Transcatheter edge to edge repair using the ease-of-use valve clamp system for functional mitral regurgitation: a primary report - Li, Wei; Long, Yuliang; Pan, Wenzhi; Wei, Lai; Pan, Cuizhen; Guan, Lihua; Zhou, Daxin; Ge, Junbo (Surgery today (Tokyo, Japan), 2023)
Purpose The ValveClamp system is a novel edge-to-edge mitral valve repair system designed for the ease of operation. We report the outcomes of our initial experience of treating functional mitral regurgitation (MR) with the ValveClamp system. Methods The subjects of this study were patients with symptomatic functional MR despite standard medical therapy, who were treated with transapical ValveClamp implantation. The patients were divided into an atrial functional mitral regurgitation (AFMR) group and a ventricular functional mitral regurgitation (VFMR) group. Clinical and echocardiographic outcomes were evaluated at baseline and then at the 3-month follow up. Results Twelve patients, with a median age of 71 years (range 65–78 years), were assigned to the AFMR group ( n = 5) or the VFMR group ( n = 7). The device implantation rate was 100%, and 10 (83.3%) patients required implantation of only one clamp. The catheter time was less than 10 min in half of the patients, the fastest time being 5 min. There were no procedure-related complications. At the 3-month follow up, all patients were free from all-cause mortality, surgery, and rehospitalization. MR improved to ≤ 2 + in all 12 patients with MR grade 3 + or 4 + at baseline, (100%) and to ≤ 1 + in 9 of these patients (75%), with a low-pressure gradient. The left atrial diameter and the left ventricular end diastolic diameter decreased significantly in both the AFMR and VFMR groups. The left ventricular eject fraction at the 3-month follow up showed a rising trend in both the AFMR and VFMR groups, whereas PASP decreased remarkably. All 12 patients with baseline NYHA functional class III/IV (100%) showed improvement of at least 1 class, and 2 of these patients (16.7%) showed improvement of at least 2 classes. Conclusions The ValveClamp system is simple and effective for transapical transcatheter edge to edge repair in patients with functional MR.